The Development of Learning Management Activities Using the Inquiry-Based Learning (5E) To Develop Analytical Thinking Skills in the Course Science and Technology for Students in Grade 3 - Namonsai, Natthanan; Intanin, Angkhan; Sanpundorn, Sasitorn (EDUCATIO : Journal of Education, 2023)
This research aims to (1) Develop learning management activities using the 5E inquiry-based learning model. science and technology course of students in grade 3. (2) Develop the analytical thinking of grade 3 students to pass the criteria of 70%. (3) To study the satisfaction of grade 3 students towards learning management using the 5E inquiry-based learning model. Thus, the researchers developed our solar system learning activities. of6- plans and developing analytical thinking skills of grade 3 students of 31 people. The results showed That (1) Learning management using the 5E quest model Amount of 6 plans and passed the evaluation of suitability efficiency by 3-experts. (2) The results of the development of analytical thinking of grade 3 students. It was found that after receiving the learning management, inquiry-based learning style 5E with an average of 7.25 representing 72.74 percent (3) Satisfaction of grade 3 students towards the learning management of the 5E inquiry-based learning model. with a high level of satisfaction.